Ethics of Modern Stem Cell Research and Therapy: Current Critical and Interdisciplinary Perspectives - Ernst, R. von Schwarz; Karine, Vartanian; Paul, Bogaardt; Aubriana, Angel Schwarz; Laurent, Cleenewerck de Kiev (Journal of Aging Research And Healthcare, 2024)
From an academic and clinical point of view, stem cell therapy represents one of the most promising advances in modern medicine, with the ability to partially induce the regeneration of acutely injured or chronically damaged tissues. Stem cell research provides new opportunities for the treatment of various conditions, among them diabetes mellitus, HIV, cardiovascular diseases, and neurodegenerative illnesses. Stem cell therapy is currently not FDA-approved in the US (except for certain blood cancers). While bioethics and religion have mostly discussed the source of cells, i.e., embryonic cells that require the destruction of embryos versus adult tissue for research purposes, we also discuss the controversies with regard to currently offered therapies, and marketing of unapproved procedures from a scientific, clinical, and religious viewpoint.
Keywords: stem cells; ethics; bioethics; religion; embryonic tissue; stem cell therapy